Trace Fossils in Permian Rocks of English Riviera UNESCO Global Geopark - Malcolm Hart; Christopher Smart (Geoconservation Research)
The Permian breccias, conglomerates and sandstones of the English Riviera UNESCO Global geopark were deposited in quite harsh, desert environments just north of the Permian Equator. Body fossil evidence is completely lacking but rare trace fossils provide evidence of a land-based community. There is a variety of traces present, probably indicative of the presence of a range of unknown animals. Though these animals cannot be identified, their occurrence is important in the understanding of the biodiversity of these Permian environments.